If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + -1) = 4x + 44 Reorder the terms: 12(-1 + x) = 4x + 44 (-1 * 12 + x * 12) = 4x + 44 (-12 + 12x) = 4x + 44 Reorder the terms: -12 + 12x = 44 + 4x Solving -12 + 12x = 44 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -12 + 12x + -4x = 44 + 4x + -4x Combine like terms: 12x + -4x = 8x -12 + 8x = 44 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 + 8x = 44 + 0 -12 + 8x = 44 Add '12' to each side of the equation. -12 + 12 + 8x = 44 + 12 Combine like terms: -12 + 12 = 0 0 + 8x = 44 + 12 8x = 44 + 12 Combine like terms: 44 + 12 = 56 8x = 56 Divide each side by '8'. x = 7 Simplifying x = 7
| 3v^2-27v+54=0 | | 3z-24(1-z)=5(1-2z)-12 | | (4x-1)+(4x-1)+(3x+2)+(3x+2)+(3x+2)=157 | | 1/3m=2/5 | | x^4-x^2=11x^2+64 | | 2x+6y=130 | | |(1/3)x-4|=2 | | 3v^2-27v+55=0 | | 4(x-2)=-1(x+3) | | 14x+4=157 | | 230-40Q=P | | 440=3w-6 | | 2n-5=4n-8-n | | 5-(4x-5)=32 | | 4(r-12)=6 | | (x-5)(x+1)=16 | | -9x+7=-6x-11 | | 0.5=-16x^2+4.5 | | -91=6(v-7)-1 | | 2x^2+4x=-12 | | (x-5)(x+1)=161 | | 76+2x+(5x-2)=180 | | f(x)=4*2 | | 3(y-2)+15=-3(y+3)+6y | | 7(-3)+2(4)= | | log(log(a))=-0.4 | | (4x-1)+(4x-1)= | | 6*(2+y)=3*(3-y) | | -3x+2(-5x)=-3 | | (c2/15)=88 | | -24+k=-4(6-8k) | | 2(n+5)+4= |